Hubungan Antara Interaksi Orang Tua Dan Anak Dengan Perkembangan Bahasa Pada Anak Usia Pra-sekolah (4-6 Tahun) Di TK Annachrowi Desa Muara Kabupaten Lebak: The Relationship Between Parent-Child Interaction and Language Development in Preschool-Age Children (4-6 Years) at Annachrowi Kindergarten, Muara Village, Lebak Regency - Badriah, Euis (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: The golden age period, at the age of 4-6 years or preschool age, is a period when the child's potential develops very rapidly. One of the most important child developments developed in early childhood is language development. However, out of a total of 12.6 million children aged 4-5 years, around 384,800 children (3,05%) have delays in language development (BPS 2010). At the age of 0-4 years, a child's brain enters a period of development, and in their development, the role of parents is very influential. The active role of parents and the environment is the right effort to optimally develop children's potential (Wintara 2017). The results of a preliminary study conducted by researchers in May 2022 at An-Nachrowi Muara Kindergarten found 10 children with delayed language development and 5 children with sufficient cognitive development.  Methods: Analysis with a cross-sectional approach with a sample of 35 respondents. The analysis technique used is the chi-square Test.  Results: Of the 80 respondents, the highest percentage of parent-child interaction was in the good category is as much as 70 children (87.23%); and the presentation of language development in preschoolers was 74 children (92.5%); indicating good language development in children. Through Bivariate analysis using the chi-square analysis test, there is a significant relationship between the interaction of parents and children with the language development of children aged 4-6 years. With a risk number of 276; which means that if the interaction between parents and children is good then there will be 275 times the chance for normal child language development compared to parent-child interaction that is lacking.  Discussion: Midwives and health workers can play a role in helping the school to provide facilitation and motivation related to parental knowledge in supporting the growth and development of children, and hope that the school, parents, and families will realize that children's development needs to be properly stimulated.